ELM 2016—data update and new functionality of the eukaryotic linear motif resource. Issue Volume 44:Issue D1(2016) (28th November 2015) - Dinkel, Holger; Van Roey, Kim; Michael, Sushama; Kumar, Manjeet; Uyar, Bora; Altenberg, Brigitte; Milchevskaya, Vladislava; Schneider, Melanie; Kühn, Helen; Behrendt, Annika; Dahl, Sophie Luise; Damerell, Victoria; et al.
Abstract: The Eukaryotic Linear Motif (ELM) resource (http://elm.eu.org ) is a manually curated database of short linear motifs (SLiMs). In this update, we present the latest additions to this resource, along with more improvements to the web interface. ELM 2016 contains more than 240 different motif classes with over 2700 experimentally validated instances, manually curated from more than 2400 scientific publications. In addition, more data have been made available as individually searchable pages and are downloadable in various formats.